Seedling quality of Pinus greggii produced in sawdust-based growing media - Vicente-Arbona, Julio César; Carrasco-Hernández, Violeta; Rodríguez-Trejo, Dante Arturo; Villanueva-Morales, Antonio (Instituto de Ecología, A.C., 2019)
In Mexico, the deforested area is high and the percentages of plant survival in reforestation programs are low. One of the key factors to increase plant survival is a good seedling quality. For the plant production in forest nurseries of Mexico, two groups of substrates are basically used: one mostly with soil (in traditional nurseries) and other with an important proportion of peat moss (technified nurseries). The first alters the natural areas already disturbed and the second is expensive. This work aims to evaluate the seedling quality of Pinus greggii Engelm. ex Parl. produced in different sawdust-based growing media, with fertilization and inoculation with an ectomycorrhizal fungus. The plants were grown in a greenhouse and evaluated after 10 months. The seedling quality was evaluated through the use of indicators, and morphological and physiological indices. Also, the physical and chemical properties of the growing media used in the present study were analyzed. In general, the seedlings were graded as medium to high quality. The treatments that obtained good grades with the highest number of quality indicators corresponded mostly to those inoculated. The best treatment corresponded to one with 80% sawdust and 20% pine bark growing media, with 8 g of controlled-release fertilizer and 75 ppm of nitrogen. It is possible to produce quality Pinus greggii seedlings with growing media based on sawdust, fertilized and inoculated with mycorrhizae fungus.